The tension between the counter-majoritarian function of constitutional justice and political power: is it possible to resolve it? - Trinidad Jiménez, Fabián (2025)
This article draws on theoretical and political references concerning the role of courts and constitutional justice in a democratic regime, particularly when they resolve disputes that affect the configuration of political power and the exercise of government by imposing political and constitutional limits, in order to highlight the tensions that arise between such jurisdictional activity and the political power of the government in office, as well as that vested in the legislative bodies. These tensions are analyzed in general terms and, in particular, with a focus on the Mexican case, characterized by a presidential system, a bicameral legislature, and popularly elected constitutional courts. with respect to which a political and governmental model is analyzed and proposed that contributes by design to alleviating these tensions and facilitates the focus of state activity toward the pursuit of a substantial democracy, a consensual or proportional democracy, attempting to overcome the authoritarian temptation of modern democracies to concentrate power and maintain it by any means except obtaining a welfare state for their population.